KESANTUNAN BERBAHASA DITINJAU DARI PRESPEKTIF KECERDASAN MAJEMUK - Eko Kuntarto (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
Politeness is not solely concerned the language proficiency but a form of multiple intelligence. In the reality of life is not a high IQ who became the only determinants ofsuccess alive. Many people who are cognitively smart but failed in life. On the contrary, many people who are cognitively average but a success in life. Theoretically, there are other factors which are thought to be the deciding one's success in life, among others, the ability to speak in a polite form of intelligence is linguistic, interpersonal, intercultural and personal. Because politeness is a form of intelligence, hence his acquisition should be through education, both in the institution of formal and non-formal. Children need to be educated to use polite language as the embodiment ofa good personal identity, in order to succeed in wading through life.This paper discusses the relationship between politeness and intelligence compounds. Some theory of politeness language (linguistic politeness theory) try combined with compound theory of intelligence (KM), which was conceived by Howard Gardner (1983). Gardner finds evidence that linguistic intelligence is one form of intelligence compound. In the perspective of theory of language, the Gardner's view can be realized in the form of politeness language. The theory is the theory that the new reatif in the field of psychology, relevant as Basic politeness in speaking.Key words: politeness, multiple intelligence, speech.